2020
DOI: 10.1088/1742-6596/1655/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Test on Several Concentrations Metarhizium anisopliae (Metsch) Sorokin in Palm oil Empty Fruit Bunch Compost (metankos) to Infecting Oryctes Rhinoceros Larvae.

Abstract: Oil palm is a very important plant because it is one of the world's vegetable oil producing plants. Oryctes rhinoceros is one of the important pests that attack oil palm plants. The recommended control of Oryctes rhinoceros is used integrate pest control, one of which can use the biological agent of the fungus Metarhizium anisopliae. The composition of oil palm empty fruit bunches can be a medium rich in organic matter for the breeding of Fungus Metarhizium anisopliae. This research aims to study the best conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…Menurut Fauzana et al (2020a), waktu awal kematian larva O. rhinoceros tercepat setelah aplikasi M. anisopliae 50 g.l -1 air pada kompos adalah 40,8 jam. Hal ini menunjukkan bahwa peningkatan konsentrasi entomopatogen M. anisopliae diatas 50 g.l -1 air yaitu 55 g.l -1 air, 65 g.l -1 air, 75 g.l -1 air, 85 g.l -1 air, dan 95 g.l -1 air tidak memberikan pengaruh kecepatan waktu awal kematian larva O. rhinoceros.…”
Section: Hasil Dan Pembahasanunclassified
See 2 more Smart Citations
“…Menurut Fauzana et al (2020a), waktu awal kematian larva O. rhinoceros tercepat setelah aplikasi M. anisopliae 50 g.l -1 air pada kompos adalah 40,8 jam. Hal ini menunjukkan bahwa peningkatan konsentrasi entomopatogen M. anisopliae diatas 50 g.l -1 air yaitu 55 g.l -1 air, 65 g.l -1 air, 75 g.l -1 air, 85 g.l -1 air, dan 95 g.l -1 air tidak memberikan pengaruh kecepatan waktu awal kematian larva O. rhinoceros.…”
Section: Hasil Dan Pembahasanunclassified
“…Hasil penelitian Fauzana et al (2020a) bahwa pada hari ketiga hingga hari kedua puluh satu pada perlakuan konsentrasi M. anisopliae 50 g.l -1 air, 40 g.l -1 air, 30 g.l -1 air, 20 g.l -1 air, dan 10 g.l -1 air, persentase kematian larva O. rhinoceros terus mengalami fluktuasi pada kisaran 2-6%. Hal ini menunjukkan bahwa peningkatan konsentrasi M. anisopliae menjadi 55 g.l -1 air , 65 Hari setelah aplikasi (HSA))…”
Section: Penambahan Mortalitas Harian Larva O Rhinocerosunclassified
See 1 more Smart Citation
“…Previous research showed that M. anisopliae with conidia density of 10 7 conidia/ml induced 6.6% to 100% O. rhinoceros larval mortality (Bintang et al, 2015). In addition, M. anisopliae application at dosages of 50 g.l -1 (302.4×10 6 conidia.ml -1 ) on O. rhinoceros larva living on empty bunches of oil palm in the field caused mortality of 56% (Fauzana et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…POEFB can be applied to palm oil plants to improve their properties and increase soil humidity so the needed composting for maximizing element nutrients on the ground can be obtained. POEFB compost and mixture with saw powder with a ratio of 50 g: 50 g added by M. anisopliae can increase the pathogenicity of O. rhinoceros larvae with total mortality of 72.5% [9]. Efforts to increase pathogenicity in controlling O. rhinoceros were carried out by adding entomopathogenic fungi M. anisopliae, following the suggestion in control using the concept of integrated pest control (IPM), namely using life of M. anisopliae which was easy to produce and develop therefore it is effective to kill O. rhinoceros.…”
Section: Introductionmentioning
confidence: 99%